Personified cognitive feedback as a powerful instrument for progressive acceleration of social evolution - Kyslenko, Y.I. (Штучний інтелект, 2018)
The concept of personified cognitive feedback (PCF) is introduced, which takes place in human neural network between the accumulated knowledge potential and new information. This feedback may always be considered as positive, taking into account experience accumulation. This connection itself provides the process of “understanding” while comparing each component and the message as a whole with the recipient’s current cognitive potential. When projecting the peculiarities of PCF realization onto the society in general, a powerful conclusion can be made that it is the multitude of separate individual PCFs with their significant creative potential and unlimited communication capabilities that enables the continuous growth of the global cognitive potential, which, in its turn, determines the “progressive acceleration of social evolution”.